IMPLEMENTATION OF “ON-FARM” METHOD FOR EARLY DETECTION OF NON-PREGNANT COWS BY A SINGLE ULTRASONOGRPHIC EXAMINATION OF THE OVARIES ON DAY 21 AFTER ARTIFICIAL INSEMINATION - DOVENSKI T.. ATANASOV B., ILIEVSKA K., STOJANOV B., JASARI B. (Wiley, 2016)
When an ultrasound is used for early pregnancy diagnosis, the emphasis must be given to idenfy non- pregnant rather than pregnant cows which allow their immediate re- inseminaon, and thus to increase the rate of successful ferlizaon. The aim of the present study was to implement an on- farm method for early detecon of non- pregnant cows by single ultrasonic examinaon of the ovaries on day 21 aer arﬁcial inseminaon. A total of 98 Holstein cows with regular estrous cycle, from three dairy farms were included in this study. The cows were scanned by B- mode “real me” ultrasound scanner equipped with 7.5 MHz trans- rectal linear probe. The cows were declared “non- pregnant” if either a “poor echogenic” Corpus Luteum (CL) with a diameter <21 mm and concomitant follicle with a diameter >15 mm were observed or absence of visible funconal CL. If a CL with “granular, grayish echogenic structure”, at least 25 mm in diameter and present follicle/s, with a diameter no larger than 13 mm was observed, the cows were considered “pregnant”. Conﬁrmaon of the test results was carried out on day 33 aer AI, also by ultrasonography. General accuracy (pregnant vs. non- pregnant) was 78.57%; however, the greatest accuracy was obtained for the “negave predicve value” with 100% of sensivity and 57.14% of speciﬁcity. Based on the results it can be concluded that this method is suitable and applicable as “on- farm” examinaon for detecon of non- pregnant cows which can be used without any addional blood or milk sampling and laboratory analysis for pregnancy diagnoses. Furthermore, all cows declared as “non- pregnant” when this method is used, could be inseminated on the same day, if a follicle larger than 17 mm is observed.